Pambansang minorya at midya ng probinsya a comparative analysis of community press reportage on the issue of local indigenous communities in Palawan - Barroso, Jeuel Zamudio; Cayaon, Carmel Jimenez
This study acknowledges that indigenous peoples in the Philippines are a marginalized sector, and that the media has the responsibility to report on the issue of such groups. It compared and analyzed the reportage of the community press on issues of the local indigenous communities in Palawan by describing the local reportage. identifying any influences which may affect the news articles to identify the significance of local reportage of IP-related issues, and recommending ways to improve said reportage. The Agenda-Setting Framing Theory and the Propaganda Model of Media Control were used as lenses in the study. Content analysis was utilized in order to examine the news articles from Palawan News, Palawan Times, and Repetek Palawan from 2015 to 2018. Semi-structured personal interviews were also conducted among the media workers and indigenous people leaders and members of Palawan to achieve a well-rounded, context-supported analysis of the local community press' reportage of indigenous peoples and their issues. Based on the data from the analysis and interviews, the researchers found that the five influences of media reportage according to Heman and Chomsky's Propaganda Model remain significant in the reportage of the three newspapers, and that the main priority are news which occur or directly affect main municipalities. Finally, resources and sourcing remain the most impactful factors on the three newspapers' reportage.